2018
DOI: 10.1093/ibd/izy091
|View full text |Cite
|
Sign up to set email alerts
|

Real-time Interobserver Agreement in Bowel Ultrasonography for Diagnostic Assessment in Patients With Crohn’s Disease: An International Multicenter Study

Abstract: In this study, the majority of the US parameters used in CD showed moderate/substantial agreement. The development of shared US imaging interpretation patterns among sonographers will lead to improved comparability of US results among centers and facilitate the development of multicenter studies and the spread of bowel US training, thereby allowing a wider adoption of this useful technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 18 publications
(27 reference statements)
3
34
0
2
Order By: Relevance
“…Our results also agree with Calabrese et al [19] who reported that Mesenteric lymph nodes are another nonspecific sign of intestinal inflammation that may be seen during active disease and chronic intestinal inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…Our results also agree with Calabrese et al [19] who reported that Mesenteric lymph nodes are another nonspecific sign of intestinal inflammation that may be seen during active disease and chronic intestinal inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…A bowel wall thickness cutoff value of 3 mm in our study showed sensitivity (83.3%), specificity (50%), and accuracy (60%) in comparison to other studies, which showed sensitivities of 88% to 94%; however, specificity (93%-97%,) and diagnostic accuracy (94%) were higher in previous studies than in our study[ 9 , 15 ]. This finding can be explained by the lack of international agreement about standardized measurement parameters, which leads to interobserver variability between examiners[ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…US is widely available and noninvasive; however, its accuracy depends on the examiner and is low in the proximal to terminal ileum region [99]. An international multicenter study reported that most US parameters used in CD showed moderate/substantial agreement [100]. Further studies will clarify the proper use of such non-ionizing radiation techniques.…”
Section: Ultrasonographymentioning
confidence: 99%